A fast and simple B–C bond formation in metallacarboranes avoiding halometallacarboranes and transition metal catalysts. Issue 11 (28th February 2020) - Buades, Ana B.; Kelemen, Zsolt; Arderiu, Víctor S.; Zaulet, Adnana; Viñas, Clara; Teixidor, Francesc
Abstract : An electrophilic substitution on metallacarboranes by using a stabilized carbocation that can be made in situ is reported for the first time. Abstract : An electrophilic substitution on metallacarboranes by using a stabilized carbocation that can be made in situ is reported for the first time. This new synthetic methodology provides a new perspective on easy metallacarborane derivatization with organic fragments, which enhances the properties of both fragments and widens their possible applications.